'Only in the Leap from the Lion's Head Will He Prove His Worth': Natural Law and International Relations. (April 2013) - Beattie, Amanda Russell
This article argues the benefits of including a theological interpretation of natural law morality within the normative discourses of international politics. It challenges the assumption of a Grotian secular natural law arguing that practical reason, in a Thomist interpretation, is better suited to the demands of international political theory. It engages with themes of agency, practical reason, and community in order to enhance the content of the post-territorial community evidenced in ethical cosmopolitan debates. Likewise, it envisions simultaneously enhancing a rapprochement among cosmopolitan and communitarian discourses of international politics facilitated through an institutional design guided by the morality of natural law.